The impact of tax pressure on long-term economic growth in Morocco - Noureddine Benkejjane; Safaa Mhatchan; Mohamed Oudgou; Abdeslam Boudhar (Economies, 2024)
Despite the tax reform in the 1980s, the Moroccan tax system still suffers from structural vulnerabilities that have led to inefficient tax policies and increasing sectoral disparities, which have led to an increase in the tax pressure rates between 1990 and 2020. To overcome these vulnerabilities, and according to the recommendations of the 2019 National Tax Conference, the Moroccan tax system has been recently restructured, with the aim of strengthening the principles of equity and tax efficiency. The main objective of this paper is to determine the impact of the tax pressure on long-term economic growth in Morocco from 1990 to 2020. To do so, the methodology adopted in this work consists of verifying the effect of the tax pressure on economic growth through a quantitative methodology based on two vector autoregression approaches: the vector autoregression model (VAR) and the vector error correction model (VECM). The results of this study confirm that the effect of fiscal pressure on economic growth in Morocco is not significant in the long run, and therefore, we can deduce that taxation is not yet a well-mastered instrument for the state to act on the economic sphere. The results show a complex relationship between tax pressures and economic growth in Morocco, underlining the importance of tax reform. However, the research is limited by the specific models and the need to explore other determinants. The contribution of this paper lies in its in-depth empirical analysis of fiscal pressure and its influence on long-term economic growth in Morocco, as based on VAR and VECM modeling. This econometric approach makes it possible to isolate the dynamic effects and responses of economic variables over time, offering an understanding of the interactions between tax policy and long-term economic growth. By focusing specifically on the Moroccan context, this study offers an original perspective and helps to fill the gap in the empirical research in this area while providing a valuable analytical framework for assessing fiscal policies and their impact on long-term economic growth.
Keywords: 330; economic growth; Engel and Granger approach; tax pressure; VAR modeling